Eradicating public official corruption Indonesia: a revolutionary paradigm focusing on state financial losses - M Zaid; Rabani M Halawa; Kartika Asmanda Putri; Fadhel Arjuna Adinda; Lamberton Cait (Wacana Hukum, 2023)
This research explores additional ways to eliminate corruption caused by authority abuse that hurts public finances. The present paradigm of corruption eradication in Indonesia still focuses on punishment, disregarding one of the Anti-Corruption Law's goals, state financial loss restitution. This research is normative, statutory, conceptual, and case-based. The results show that the administrative law approach to eradicating criminal acts of corruption due to government official abuse of authority focuses more on returning state losses through initial supervision by internal government agencies, such as the Government Internal Supervisory Apparatus. APIP has direct prosecution and compensation powers. The Supervisory Agency (BPK) finds state financial losses, it is better to take administrative action to recover them by communicating with APIP for time efficiency in eradicating corruption and recovering state losses. Third, sanctions in the authority that results in state financial losses are contained in Article 20 Juncto 21 of Law Number 30 of 2014 concerning governance, which only provides administrative sanctions of dismissal and does not require government officials to return state financial losses.